VOLATILITAS HARGA KOMODITAS PANGAN DAN IMPLIKASINYA TERHADAP KEBIJAKAN STABILISASI PANGAN DI PROVINSI BANTEN - Firman Emmanuel Declarantius Parulian; Marchadha Santi Wilda (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2026)
National food security requires controlled price stability to ensure public purchasing power. However, Banten Province continues to face serious challenges, evidenced by a decline in the Food Consumption Pattern (PPH) score and the Food Security Index (IKP) due to extreme commodity price volatility. This study aims to analyze the volatility characteristics of eight primary food commodities: shallots, garlic, red chili, bird's eye chili, chicken meat, beef, chicken eggs, and granulated sugar in Banten Province from July 2017 to December 2025. Employing a quantitative approach using the ARIMA-EGARCH model, this research specifically identifies the presence of asymmetric (leverage) effects in price dynamics. The results indicate that all eight commodities exhibit ARCH effects, with the EGARCH model identified as the most suitable fit. Beef shows the highest leverage value (0.624), demonstrating the greatest responsiveness to price shocks compared to other commodities. In contrast, chicken eggs and granulated sugar exhibit lower volatility levels. Uniquely, shallots are more susceptible to